Panel Method for 3D Inviscid Flow Simulation of Low-Pressure Compressor Rotors with Tip-Leakage Flow - Valentin Caries; Jérôme Boudet; Eric Lippinois (International Journal of Turbomachinery, Propulsion and Power)
This paper presents a low-order three-dimensional approach for predicting the inviscid flow around low-pressure compressors. The method is suitable for early design stages and allows a broad exploration of design possibilities at minimal cost. It combines the vortex lattice method with the panel method by using a mixed boundary condition. In addition, it models the tip-leakage flow using an iterative algorithm. First, the verification of the approach is carried out on a low-pressure compressor configuration. The wake length is a decisive parameter for ensuring correct flow deflection in ducted applications. A periodicity condition is introduced and validated, which reduces the computational and memory requirements. On average, the calculations take less than one minute in real time. The approach is validated on the same low-pressure compressor configuration. A good agreement is obtained with RANS concerning the mean flow and the tip-leakage flow characteristics. Sensitivity to the mass flow rate is also fairly well predicted, although discrepancies develop at lower mass flow rates.